2015
DOI: 10.1016/bs.pmbts.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in the Cornea

Abstract: The cornea is the tough, transparent tissue through which light first enters the eye and functions as a barrier to debris and infection as well as two-thirds of the refractive power of the eye. Corneal damage that is not promptly treated will often lead to scarring and vision impairment. Due to the limited options currently available to treat corneal scars, the identification and isolation of stem cells in the cornea has received much attention, as they may have potential for autologous, cell-based approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 102 publications
0
36
0
1
Order By: Relevance
“…(See review. 132 ) A recent study has shown that these limbal stromal progenitors also possess the potential of being reprogrammed into CK3/CK12-expressing (cornea-like) epithelial cells. 133 …”
Section: In Vitro Reconstitution Of Limbal Nichementioning
confidence: 99%
“…(See review. 132 ) A recent study has shown that these limbal stromal progenitors also possess the potential of being reprogrammed into CK3/CK12-expressing (cornea-like) epithelial cells. 133 …”
Section: In Vitro Reconstitution Of Limbal Nichementioning
confidence: 99%
“…MSCs can be isolated from multiple tissues, including adipose tissue and bone marrow. Our previous work has shown that human corneal stroma contains a population of cells (human corneal stem cells, CSSC), which exhibit properties of MSCs and differentiate to corneal keratocytes [2][3][4][5][6][7][8][9]. These cells also block deposition of opaque scar tissue in a corneal wound healing model and elicit regeneration of normal, transparent stromal extracellular matrix [7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that human corneal stroma contains a population of cells (human corneal stem cells, CSSC), which exhibit properties of MSCs and differentiate to corneal keratocytes [2][3][4][5][6][7][8][9]. These cells also block deposition of opaque scar tissue in a corneal wound healing model and elicit regeneration of normal, transparent stromal extracellular matrix [7,8,[10][11][12]. An important aspect of tissue regeneration effected by MSCs depends on their modification of tissue immune response by secretion of soluble factors to their environment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This collar of tissue is endowed with specialised functions including (i) maintenance of epithelial mass through the activity of limbal epithelial stem cells, (ii) supplying nutrients and chemical mediators to the avascular cornea through its extensive vascular network1 and (iii) immune surveillance by inflammatory cells 2. The corneal stroma comprises ∼90% of corneal thickness and contains a heterogeneous population of cells, the vast majority of which are resident neural crest-derived keratocytes, and a rarer population of primitive fibrocytes that reside proximal to the limbus and express markers of bone marrow-derived mesenchymal stem cells 3. These cells are responsible for regenerating the corneal stroma under steady state,3 and following pathological insults, they regulate inflammation through their immunosuppressive properties 3.…”
Section: Introductionmentioning
confidence: 99%
“…The corneal stroma comprises ∼90% of corneal thickness and contains a heterogeneous population of cells, the vast majority of which are resident neural crest-derived keratocytes, and a rarer population of primitive fibrocytes that reside proximal to the limbus and express markers of bone marrow-derived mesenchymal stem cells 3. These cells are responsible for regenerating the corneal stroma under steady state,3 and following pathological insults, they regulate inflammation through their immunosuppressive properties 3. Dendritic cells (DCs) are also resident to the cornea;4 5 these ‘professional’ antigen-presenting cells tend to congregate within the limbal stroma but are also found within the corneal epithelium6 and play a pivotal role in immune surveillance.…”
Section: Introductionmentioning
confidence: 99%